THE EFFECT OF EXERCISE PROGRAMS ON THE FUNCTIONALITY OF PRE-FRAGILE AND FRAGILE OLDER ADULTS (REMUNOM, 2026)
Population aging is associated with an increased prevalence of conditions such as pre-frailty and frailty, which directly impact the functional status of older adults. The aim of this study was to analyze the effects of physical exercise programs on the functional status of pre-frail and frail older adults. This is an integrative literature review conducted in the PEDro, PubMed/Medline, and BVS databases, including studies published between 2015 and 2025. After applying the eligibility criteria, four clinical trials were included in the analysis. The results showed that physical exercise programs promote significant improvements in physical performance, muscle strength, balance, and walking speed. Additionally, a reduction in the risk of falls and improvements in functional aspects were observed. Thus, physical exercise proves to be an effective strategy for improving and maintaining functionality, as well as for delaying the progression of pre-frailty and frailty in older adults.